Anmeldelser - Aktor, Mikael; Bjørnvig, Thore; Bønding, Sophie; Davidsen, Markus; Madsen, Lars; Nielsen, Marie Vejrup; Petersen, Anders Klostergaard; Thomsen, Søren Feldtfos (Religionsvidenskabeligt Tidsskrift, 2012)
n/a